2006
DOI: 10.2146/ajhp050403
|View full text |Cite
|
Sign up to set email alerts
|

Applying antimicrobial pharmacodynamics to resistant gram-negative pathogens

Abstract: Various mechanisms account for resistance of bacteria to antibiotics. The appropriate use of pharmacokinetics and pharmacodynamics can guide antibiotic therapy and enhance the likelihood of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Using knowledge of MIC of antibiotics has shown to optimize antimicrobial choice and dose to ensure the best use of our dwindling anti-infective resources[23]Understanding of time- and concentration-dependent antibiotic concepts needs to be inculcated in the practice of the treating physiciansContinuous infusion of β-lactam antibiotics, rather than the bolus dose, should be practiced as it may improve outcomes because of its time-dependent antibacterial activity. It has been shown that continuous infusion of vancomycin was associated with less adverse effects and nephrotoxicity in children[2024]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using knowledge of MIC of antibiotics has shown to optimize antimicrobial choice and dose to ensure the best use of our dwindling anti-infective resources[23]Understanding of time- and concentration-dependent antibiotic concepts needs to be inculcated in the practice of the treating physiciansContinuous infusion of β-lactam antibiotics, rather than the bolus dose, should be practiced as it may improve outcomes because of its time-dependent antibacterial activity. It has been shown that continuous infusion of vancomycin was associated with less adverse effects and nephrotoxicity in children[2024]…”
Section: Resultsmentioning
confidence: 99%
“…Using knowledge of MIC of antibiotics has shown to optimize antimicrobial choice and dose to ensure the best use of our dwindling anti-infective resources[23]…”
Section: Resultsmentioning
confidence: 99%
“…13 In addition, older studies did not differentiate between the preferred form, colistimethate sodium, and its toxic form, colistin sulfate. 15 Current data indicate that the high rate of nephrotoxicity once associated with colistin use is dose dependent and reversible upon discontinuation. 22,27 While current guidelines recommend colistin to be given 1.5 to 5 mg/kg/day, higher doses were typically reported in older data with higher incidences of toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…The last published data were available in 1981 and later withdrawn due to rare use and the complexity of the antibacterial activities of colistimethate sodium's metabolite. 8,11,15,16 The re-released susceptibility break points are defined as “susceptible” with MIC less than or equal to 2 mcg/mL, “intermediate” with MIC of 4 mcg/mL, and “resistant” with MIC greater than or equal to 8 mcg/mL. The document still does not report break points for other bacteria, including Acinetobacter species.…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…The overuse of antibiotics may result in the generation of antibiotic-resistant bacterial strains, with severe consequences. 2,3 Antibiotic resistance-related problems have become a worldwide concern. 4,5…”
Section: What Is Known and Objectivementioning
confidence: 99%